Study of Band Gap of Silver Nanoparticles—Titanium Dioxide Nanocomposites. (9th April 2014) - Barone, P.; Stranges, F.; Barberio, M.; Renzelli, D.; Bonanno, A.; Xu, F.
Abstract : The optical and chemical properties of Ag/TiO2 nanocomposites were investigated to explore the possibilities of incorporating these new materials in Gratzel photoelectrochemical cells. The nanocomposites were obtained doping TiO2, in both allotropic species anatase and rutile, with silver nanoparticles (grown by laser ablation process). X-ray photoelectron data indicate the absence of Ag-Ti chemical bonds, while measurements of photoluminescence and optical absorbance in UV-visible range show a quench in photoluminescence emission of about 50% and an increase in visible absorbance of about 20%. Measurements of optical band gap, obtained by Tauc's equation, indicate a variation of about 1.6 eV.